A Grammar of Yélî Dnye The Papuan Language of Rossel Island - Levinson, Stephen C. (Pacific Linguistics [PL], 2022)
This is a comprehensive description of a language spoken offshore from Papua New Guinea, remarkable for its phonological, morphological and syntactic complexity. As the sole surviving member of its language family, it provides unique evidence for the kind of languages spoken in this part of the world before the Austronesian expansion. The grammar provides detailed information on phoneme inventory, morphology, syntax and select semantic fields.